2011
DOI: 10.1016/j.molimm.2011.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Factor H gene variants in Japanese: Its relation to atypical hemolytic uremic syndrome

Abstract: Mutations and polymorphisms of factor H gene (FH1) are known to be closely involved in the development of atypical hemolytic uremic syndrome (aHUS). Several groups have identified disease risk mutations and polymorphisms of FH1 for the development of aHUS, and have investigated frequencies of aHUS in a number of ethnic groups. However, such studies on Japanese populations are limited. In the present study, we analyzed FH1 in Japanese aHUS patients and healthy volunteers, and examined whether those variants imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…In 2008, Mukai et al reported the predisposing mutation of CFH in a 1-year-old female aHUS patient by using both hemolytic assay and genetic analysis [69]. Further study was performed by Fujimura et al, who have studied Japanese patients with TMA by measuring ADAMTS13 activity since 1998.…”
Section: Current Studies For the Patients With Ahus In Japanmentioning
confidence: 99%
“…In 2008, Mukai et al reported the predisposing mutation of CFH in a 1-year-old female aHUS patient by using both hemolytic assay and genetic analysis [69]. Further study was performed by Fujimura et al, who have studied Japanese patients with TMA by measuring ADAMTS13 activity since 1998.…”
Section: Current Studies For the Patients With Ahus In Japanmentioning
confidence: 99%
“…Patients with aHUS have also been reported in Japan [3], and a series of cases prompted the Japanese Society of Nephrology and the Japan Pediatric Society to jointly develop the aHUS diagnostic criteria in 2013 [4,5]. These criteria broadly defined aHUS as a TMA condition unrelated to STEC-HUS or TTP; thus, the definition included aHUS with complement regulation abnormality and TMA with coexisting diseases (secondary TMA; also called other TMA).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with aHUS have also been reported in Japan, and a series of cases prompted the Japanese Society of Nephrology and the Japan Pediatric Society to jointly develop the aHUS diagnostic criteria in 2013 . These criteria broadly defined aHUS as a TMA condition unrelated to STEC‐HUS or TTP; thus, the definition included aHUS with complement regulation abnormality and TMA with coexisting diseases (secondary TMA; also called other TMA).…”
mentioning
confidence: 99%